Cannabis and cognitive dysfunction: Parallels with endophenotypes of schizophrenia? - Solowij, Nadia (2007)
Currently, there is a lot of interest in cannabis use as a risk factor for the development of schizophrenia. Cognitive dysfunction associated with long-term or heavy cannabis use is similar in many respects to the cognitive endophenotypes that have been proposed as vulnerability markers of schizophrenia. In this overview, we examine the similarities between these in the context of the neurobiology underlying cognitive dysfunction, particularly implicating the endogenous cannabinoid system, which plays a significant role in attention, learning and memory, and in general, inhibitory regulatory mechanisms in the brain. Closer examination of the cognitive deficits associated with specific parameters of cannabis use and interactions with neurodevelopmental stages and neural substrates will better inform our understanding of the nature of the association between cannabis use and psychosis. The theoretical and clinical significance of further research in this field is in enhancing our understanding of underlying pathophysiology and improving the provision of treatments for substance use and mental illness.